2013
DOI: 10.1038/srep01114
|View full text |Cite
|
Sign up to set email alerts
|

S100+ cells: A new neuro-immune cross-talkers in lymph organs

Abstract: Up to now, the ‘hardwired’ neural pathway of the neuro-immune regulation is not fully understood. Here we reported a new neural pathway which links sympathetic nerves with immune cells of the lymphoid tissues. Our results demonstrated that nerve fibers derived from superior cervical ganglion directly targeted only S100+ cells in the cervical lymph nodes. Moreover, we found co-expression of neurotransmitters such as norepinephrine, vasoactive intestinal polypeptide and neuropeptide Y in the postganglionic sympa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
1
22
1
1
Order By: Relevance
“…4 (c) and (d)), which additionally confirms the stability of the model drug loading under cell culture conditions. 29 This lack in the uptake of free model drug at dye concentration levels present in the supernatant after release indicates that a cellular uptake of drugs is favored by intracellular release of drugs from loaded particles from the film surface under the studied conditions, fully in line with previously reported results obtained for spin-coated particulate films. 16 The possibility of particle-mediated transport of drugs was investigated by further cell experiments.…”
Section: Drug Loading and Releasesupporting
confidence: 90%
“…4 (c) and (d)), which additionally confirms the stability of the model drug loading under cell culture conditions. 29 This lack in the uptake of free model drug at dye concentration levels present in the supernatant after release indicates that a cellular uptake of drugs is favored by intracellular release of drugs from loaded particles from the film surface under the studied conditions, fully in line with previously reported results obtained for spin-coated particulate films. 16 The possibility of particle-mediated transport of drugs was investigated by further cell experiments.…”
Section: Drug Loading and Releasesupporting
confidence: 90%
“…Compared with another study of the sympathetic innervation of rat cervical lymph nodes by using anterograde tracking of nerves with Fluoro-Ruby (a neuronal tracer) 34 revealing the varicosities (nerve endings) of sympathetic fibers only, our study has not only demonstrated the distribution of NMSC/Remak fibers, but also revealed another kind of NMSC-immune cell contact. Compared with another innervation study of the lymph node by means of an anti-NF antibody, 14 we have also observed more NMSCs including cell bodies and processes inside the B cell follicle; this might also indicate the additional presence of more nerve fibers in the cortex region including B cell follicles and their Germinal centers.…”
Section: Discussionmentioning
confidence: 75%
“… 1-2 ,6, 10 These tight microanatomical connections between the cells of the two systems provide the structural support of the complex network of immune responses. Until now, despite some reported studies, 11 , 13 , 14 , 34 , 35 detailed microanatomical descriptions of innervation of lymph nodes have been limited. By using anti-GFAP as a reliable cellular marker, we have analyzed the distribution of NMSCs in the mesenteric lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…4(c) and (d)), which additionally conrms the stability of the model drug loading under cell culture conditions. 34 The lack of free model drug in the supernatant indicates that the drug must be delivered to the cells according to a different mechanism. Previous studies have reported that a cellular uptake of hydrophobic drugs is favored by intracellular release of drugs from loaded particles taken up from the lm surface.…”
Section: Model Drug Loading and Releasementioning
confidence: 99%